Association of germline genetic variants with breast cancer-specific survival in patient subgroups defined by clinic-pathological variables related to tumor biology and type of systemic treatment - Morra, Anna; Escala-Garcia, Maria; Beesley, Jonathan; Keeman, Renske; Canisius, Sander; Ahearn, Thomas U; Andrulis, Irene L; Anton-Culver, Hoda; Arndt, Volker; Auer, Paul L; Augustinsson, Annelie; Beane Freeman, Laura E; et al. (Springer Science and Business Media LLC, 2021)
Given the high heterogeneity among breast tumors, associations between common germline genetic variants and survival that may exist within specific subgroups could go undetected in an unstratified set of breast cancer patients.